In situ temperature profile measurements with high‐energy X‐rays as a probe of optical floating zone crystal growth environment. Issue 4 (16th July 2020) - Denney, Jonathan J.; Wang, Yusu; Corrao, Adam A.; Huang, Guanglong; Montiel, David; Zhong, Hui; Dooryhee, Eric; Thornton, Katsuyo; Khalifah, Peter G.
Abstract : A new synchrotron‐compatible furnace for simulating the environment inside an optical floating zone furnace is described. It is shown that temperature profiles within heated rods can be determined from in situ synchrotron diffraction data, and that these measured profiles can be reproduced with a four‐component heat‐transfer model. Abstract : The ability of optical floating zone (OFZ) furnaces to rapidly produce large single crystals of complex emerging materials has had a transformative effect on many scientific fields that require samples of this type. However, the crystal growth process within the OFZ furnace is not well understood owing to the challenges involved in monitoring the high‐temperature crystal growth process. Novel beamline‐compatible optical furnaces that approximate the inhomogeneous growth environment within an OFZ furnace have been fabricated and tested in high‐energy synchrotron beamlines. It is demonstrated that temperature profiles can be effectively extracted from powder diffraction data collected on polycrystalline ceramic rods heated at their tip. Furthermore, these measured temperature profiles can be accurately reproduced using a heat‐transfer model that accounts for solid‐state thermal conduction, partial sample lamp power absorption, convective air cooling and radiative cooling, allowing key thermal parameters such as thermal conductivity to be extracted from experimental data.